Male Reproductive Cancers Epidemiology, Pathology and Genetics - Foulkes, William D.; Cooney, Kathleen A.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2010)
Male Reproductive Cancers: Epidemiology, Pathology and Genetics presents a thoughtful, comprehensive and up-to-date overview of the etiology of the prostate gland and the testes, summarizing decades of research in the three most important etiological disciplines: epidemiology, pathology and genetics. This book is comprised of four distinct sections: Epidemiology, Pathology, Molecular Genetics, and Inherited Susceptibility, with each section divided into chapters categorized by disease. Section A reviews the epidemiology of prostate and testicular cancer, with an emphasis on clinical and environmental factors associated with these diseases. Section B begins by describing various pathological features of prostate cancer, followed by descriptions of the wide variety of testicular cancers as well as a brief section on the use of tumor markers for monitoring disease. Section C focuses on somatic genetic changes in prostate and testicular cancers using new technologies such as comparative genomic hybridization and gene expression profiling. Section D concentrates on the progress made toward understanding inherited susceptibility to prostate cancer and to testicular cancer.
Epidemiology -- The Epidemiology of Prostate Cancer -- The Epidemiology of Testicular Cancer -- Pathology -- Prostate Cancer: A Pathological Perspective -- Testicular Tumor Pathology -- Molecular Genetics -- Somatic Molecular Genetics of Prostate Cancer -- Molecular Genetics of Testicular Germ Cell Tumor -- Inherited Susceptibility -- Identification of Genetic Risk Factors for Prostate Cancer: Analytic Approaches Using Hereditary Prostate Cancer Families -- The Identification of Rare and Common Variants Which Predispose to Prostate Cancer -- Prostate Cancer in Special Populations -- Inherited Susceptibility of Aggressive Prostate Cancer -- Susceptibility Alleles for Testicular Germ Cell Tumor.
Keywords: Medicine; Oncology; Human genetics; Biomedicine; Cancer Research; Human Genetics; Oncology